Strategi Penyaluran Zakat Terhadap Janda-Janda Tua Duafa Pada Lembaga Amil Zakat Nurul Hayat Desa Sempusari Kecamatan Kaliwates Kabupaten Jember Dalam Upaya Pemberdayaan Ekonomi - Aminatus Zahriyah; Moh. Zuhdi; Mohamad Hidayatullah (GLOBAL SCIENTS PUBLISHER, 2024)
The method of distributing zakat is various ways, directly and indirectly. All methods in general how zakat can be realized properly according to their respective conditions that demand to be in harmony with local circumstances. In particular, zakat serves as the fulfillment of the rights of people who are entitled to receive zakat. In Islamic law not everyone has the right to receive zakat, only certain people are worthy of receiving and belong to the weak. Those who are entitled to receive zakat are fakir, poor, muallaf, riqab (slaves), gharimun (people who have debts), travelers, amil, fi sabilillah, ibn sabil. From that, the number of zakat recipients, so there are also various methods of realizing it, this depends on each mustahiq in all its conditions. Nurul Hayat as a zakat distribution institution has a SAJADA (Santunan Janda Tua Duafa) program which is engaged in empowering old widows in an effort to fulfill their rights economically by providing compensation in the form of rp. 50,000 and basic necessities every month carried out every 10th. This empowerment focuses on poor elderly widows who are out of work and economic limitations aged 60 and over. This is in line with the purpose and obligation as an amil zakat institution and the legal obligation to pay special attention to the duafa, not only that Nurul Hayat is obliged to collect zakat from people who are obliged to pay zakat so that the distribution and empowerment program runs smoothly including compensation to poor old widows, in line with the sound of verses in the Qur'an surah Al-Baqarah 267